Modularity clustering of economic development and ESG attributes in prefabricated building research - Li, Rita Yi Man; Li, Bo; Zhu, Xiaoe; Zhao, Jingjing; Pu, Ruihui; Song, Lingxi (Frontiers in Environmental Science, 2022)
Many countries are using different approaches to achieve the goal of sustainability and safety. About two-third institutional investors anticipate that environmental, social and governance (ESG) will become part of the industry standard. One main change in the modern construction industry worldwide is moving toward prefabricated buildings (offsite construction) to achieve sustainable development. When most work processes are completed factory indoor, wastage and accidents due to uncertain outdoor climate change could be reduced substantially. While there are researches threw light on prefrabicated building and the industry aware of ESG, there is no systematic research reviewed the state-of-art research in ESG incorporation in prefrabricated buildings or impact of economic development on prefrabricated buildings’ development. This gap is filled by visualizing the articles’ titles, authors, keywords, abstracts, and references from WoS and Scopus. It also included modularity cluster and an evolution of this field analysis. Based on the science map modularity cluster analysis, prefabricated buildings are the most mentioned topic in developing countries and cost control is still the most concerning issue in both developed and developing countries. This study is the first that advocates the idea of EESG (economics ESG), that is apart from considering ESG when companies make decisions, it may be more appropriate to consider economics concern as well. It offers recommendations for related companies for their future strategy and provides future research direction.